Aerodynamic noise evaluation for Aeolian tone and acoustical insulating plate by similarity law - Akitoshi MATSUI (The Japan Society of Mechanical Engineers, 2020)
The objective of this research is to assess aerodynamic noise sources and the wind velocity conversion of the similarity law in an increasing wind velocity. We measured the aerodynamic noise that radiates from cylinders with and without periodic holes and a pantograph model with and without a sound insulating plate in a low-noise high-speed wind tunnel. The noise level of the cylinders was in proportion to the sixth power of wind velocity because the cylinders acted as a dipole sound source. The effect of noise reduction caused by the change in flow structure, that is, the periodic holes, also continued. However, the second peak noise radiating from the cylinder was in proportion to the sum of the sixth power and the eighth power of wind velocity and was underestimated by wind velocity conversion based on a dipole sound source. The noise level of the pantograph model with the sound insulating plate was in proportion to lower than the sixth power of wind velocity in contrast to the pantograph model itself. This is because the noise reduction effect of the sound insulating plate had a frequency characteristic. In this research, when increasing the wind velocity, the dominant pantograph noise frequency region shifted to a higher level, and the dominant noise level began to be affected by the noise reduction of the sound insulating plate. This caused the reduction effect of the sound insulating plate to be underestimated by 2.5 dB due to the noise level conversion of wind velocity. To solve this problem, the plate’s theoretical reduced noise level, which was calculated by using the Fresnel number, was subtracted from the estimated noise level of the pantograph itself. This lead to pantograph noise with the sound insulating plate being estimated within a 0.8-dB difference.